Measuring the frequency dynamics of financial and macroeconomic connectedness - Jozef Barunik; Tomas Krehlik (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We propose a general framework for measuring frequency dynamics of connectedness in economic variables based on spectral representation of variance decompositions. We argue that the frequency dynamics is insightful when studying the connectedness of variables as shocks with heterogeneous frequency responses will create frequency dependent connections of different strength that remain hidden when time domain measures are used. Two applications support the usefulness of the discussion, guide a user to apply the methods in different situations, and contribute to the literature with important findings about sources of connectedness. Giving up the assumption of global stationarity of stock market data and approximating the dynamics locally, we document rich time-frequency dynamics of connectedness in US market risk in the first application. Controlling for common shocks due to common stochastic trends which dominate the connections, we identify connections of global economy at business cycle frequencies of 18 up to 96 months in the second application. In addition, we study the effects of cross-sectional dependence on the connectedness of variables.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C18; C58; G15; 330; connectedness; frequency; spectral analysis; market risk; business cycles